Risk-informed based comprehensive path-planning method for radioactive materials road transportation. (March 2022) - Tao, Longlong; Wu, Jie; Ge, Daochuan; Chen, Liwei; Sun, Ming
Highlights: Multi-objective route planning indicators are established for radioactive material road transportation considering radiological risk cost, transportation time cost, and economical cost. A novel integrated probabilistic safety assessment (PSA) methodology framework is proposed for the radiological risk cost estimation. To obtain the risk, the accident sequence-based probability analysis model and the PEHR comprehensive severity index-based radiological consequence evaluation model are established. The proposed RICPP methodology is beneficial for selecting a safer and more economical route for radioactive materials road transportation. Abstract: The optimization of transportation routes of radioactive materials (RADMAT) is recognized as one of the most important measures to reduce the radioactive risks and costs during transportation. However, the route optimization indicators have not been fully considered and quantified in current researches. Here, we propose a Risk-Informed based Comprehensive Path-Planning method (RICPP) for RADMAT Road Transportation (RMRT) route optimization by considering radiological risk cost, time cost, and economical cost. Among which, the ET/FT based Probabilistic Safety Assessment (PSA) model is established to quantitatively assess the accident occurrence probability, and then the PEHR (personnel, environment, hazard target, and rescue force) comprehensive severity indexes considering vulnerability and resilience are established and quantified to characterize the accident radiological consequence. Finally, the gray relation analysis (GRA) model is employed to select an optimal path considering the multi-objective route planning indicators. The case study results show that the obtained path could reasonably reduce risks and costs during the transportation process, which demonstrates the effectiveness of the proposed method. The proposed RICPP methodology is beneficial for selecting a safer and more economical route for radioactive materials road transportation.